Environment-friendly Fully Biodegradable Jute-Poly(vinyl Alcohol) Modified Soy Composite Development as Plastic Substitute. Issue 3 (4th March 2022) - Behera, Ajaya Kumar; Sen, Ramkrishna; Adhikari, Basudam
ABSTRACT: The aim of this investigation was to develop composites with high mechanical strength and complete biodegradation property. Mild alkali-treated jute and poly(vinyl alcohol)-modified nanoclay-based soy resins were used to develop jute-modified soy composites. The tensile strength of composite was enhanced up to 75% and impact strength by 30% as compared to that of normal jute–soy composite. Biodegradation study was carried out by soil burial condition. These composites can be used in different sector as replacement of nonbiodegradable plastic.